Karakteristik Sifat Kimia dan Organoleptik Bakso Daging Ayam Afkir yang Ditambahkan Tepung Bonggol Pisang (Musa Paradisiaca) Sebagai Pengganti Tepung Tapioka: Characterististics Chemical and Organoleptict Properties of meatballs from rejected Chicken Added Banana Weevil Flour (Musa paradisiaca) as a Substitute of Tapioca Flour - Afriana Bui Taek; Heri Armadianto; Bastari Sabtu (Jurnal Peternakan Lahan Kering, 2023)
The purpose of this study was to look at the chemical and organoleptic qualities of meatballs fromrejected chicken added with banana weevil flour as a substitute for tapioca flour. A CompletelyRandomized Design (CRD) with 5 groups and 3 replications was applied in the study. The treatmentconsisted of P0= 40% tapioca flour + 0% banana hump flour, P1= 30% tapioca flour + 10% bananaweevil flour, P2= 20% tapioca flour + 10% banana weevil flour, P3= 10% tapioca flour + 30% bananaweevil flour, P4 = 0% tapioca flour + 40% banana weevil flour. The variables studied were chemicalquality tests (amylopectin, carbohydrates and elasticity) and organoleptic tests (taste, aroma and color).The results showed that substitution of banana weevil flour had a significant effect (P<.0.05) on thechemical and organoleptic quality of meatballs from rejected chicken. 40% replacement of tapiocaflour with banana weevil flour in meatball processing can increase carbohydrates, amylopectin, andelasticity but decrease taste, color and aroma scores.Banana weevil flour which replaces tapioca in theprocessing of meatballs and substitution at a level of 40% can increase carbohydrates, amylopectin,and elasticity and decrease the taste, color and aroma scores. Maksud dari penelitian ini adalah untuk melihat kualitas kimia dan organoleptik bakso daging ayamafkir yang ditambahkan tepung bonggol pisang sebagai pengganti tepung tapioka. Rancangan AcakLengkap (RAL) dengan 5 kelompok dan 3 kali ulangan digunakan dalam penelitian ini. Perlakuanterdiri dari P0= 40% tepung tapioka + 0% tepung bonggol pisang, P1= 30% tepung tapioka + 10%tepung bonggol pisang, P2= 20% tepung tapioka + 10% tepung bonggol pisang, P3= 10% tepungtapioka + 30% tepung bonggol pisang, P4= 0% tepung tapioka + 40% tepung bonggol pisang. Variabelyang diteliti adalah uji kualitas kimia (amilopektin, karbohidrat dan kekenyalan) dan uji organoleptik(rasa, aroma, dan warna). Hasil penelitian mengungkapkan bahwa substitusi tepung bonggol pisangmemberi pengaruh signifikan (P<0,05) pada kualitas kimia serta organoleptik bakso daging ayamafkir. Tepung bonggol pisang yang menggantikan tapioka dalam pengolahan bakso dan substitusi padalevel 40% dapat meningkatkan karbohidrat, amilopektin, dan kekenyalan dan menurunkan skor rasa,warna dan aroma.